(untitled) (KONFERENSIYA, 2026)
Achieving collocational competence is crucial for EFL learners to achieve native-like fluency as well as minimize the time and cognitive effort taken, which, in turn, develops better comprehension and production. This research examines the utilization of video content to enhance the acquisition of English collocations in EFL courses, while also endeavoring to formulate diverse methodologies for defining collocations as well as the challenges to be faced in the process. The results demonstrate that video-assisted education improves both receptive and productive collocational proficiency. The research argues that video integration functions as both a genuine and contextual language input while enhancing lexical and collocational competence. The incorporation of video content into collocational training requires further research.